Carbon Sequestration Potential of Different Plantation Tree Species in Western Ethiopia - Semere, Mihert; Dejene, Tatek; Bahru, Tinsae; Kidane, Berhane (Brawijaya University, 2024)
Plantations of fast growing tree species are imperative in climate change mitigation efforts as of their enormous potential for carbon storage and, this potential largely affected by tree species type. This study estimates biomass and soil organic carbon (SOC) under fast-growing tree species in western Ethiopia. Parameters, height (H) and diameter at breast height (DBH) were measured in permanently plots to evaluate the biomass carbon stock of selected species. Soil samples (0–15 and 15-30 cm) were also collected to determine soil organic carbon (SOC) and bulk density. Above and below-ground biomass (AGB) and (BGB) were estimated using the species-specific allometric equations while SOC was analysed in the laboratory. The results showed that the highest biomass carbon stock was recorded for Eucalyptus globulus (5.7Mg C ha-1) and the lowest was recorded for Eucalyptus grandis (1.2 Mg C ha-1). The highest and lowest mean total soil organic carbon (SOC) was recorded for Eucalyptus saligna (60 Mg C ha-1), and Eucalyptus viminalis (35.4 Mg C ha-1), respectively. This study revealed plantation sites could enhance carbon stock accumulation both in the biomass and soil organic carbon. Hence, considering of incorporating fast growing tree species in plantations is useful in climate change mitigation strategies.